Rethinking non-urgent EMS conveyance to ED during night-time - a pilot study in Southwest Finland - Kasvi Aleksi; Iirola Timo; Nordquist Hilla (BMC, 2025)
Background: The amount of emergency medical service missions has increased internationally in recent years, and emergency departments are overcrowded globally. Previous evidence has shown that patients arriving at the emergency department during nighttime (20 - 08) have to wait longer, are more likely to leave without being seen, and often have non-urgent conditions compared to patients arriving during the day. The objective of this pilot study was to examine what kind of patient groups are conveyed as non-urgent to the hospital by emergency medical service during nighttime and what kind of diagnostic tests and medical interventions those patients receive before morning to identify patient groups that could be non-conveyed or directed to alternative points of care.
Methods: This was a retrospective register study where the information of patients conveyed to university hospital during nighttime (20 - 08) were analyzed. Frequencies of the dispatch codes presenting complaints, medical treatments, and diagnostic tests were calculated. Age significance (under/over 70 years) was also tested.
Results: 73.5% of the patients received neither medical treatment nor had diagnostic tests taken before morning. Most of these were patients with mental disorder(s), hip pain/complaint, or laceration/cut. Almost half of the patients with abdominal pain or fever had laboratory tests taken. Patients over 70 years old received more medications and had more diagnostic tests taken than younger patients.
Conclusions: Some of the low-acuity patients could be non-conveyed or referred to alternative pathways of care to avoid impolitic use of emergency medical service and to reduce the workload of emergency departments. Further research is needed to ensure patient safety for patients who are not conveyed at night.